IL-38 as a Novel Biomarker in Multiple Myeloma Patients: A Prospective Clinical Evaluation - Shen H; Zhao P; Cao J (Cancer Management and Research)
Hailan Shen, Ping Zhao, Ju Cao Department of Laboratory Medicine, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Ju Cao, Department of Laboratory Medicine, The First Affiliated Hospital of Chongqing Medical University, No. 1 You-Yi Road, Yu-zhong District, Chongqing, 400016, People’s Republic of China, Tel +86-15213151261, Fax +86-023-89012513, Email caoju723@163.comIntroduction: Multiple myeloma (MM) is a refractory haematological malignancy. Interleukin 38 (IL-38) is a novel cytokine that has attracted significant research in recently years. However, no study has investigated IL-38 expression in MM. This study aims to investigate the expression of IL-38 in MM and to provide valuable insights for clinical treatment and efficacy evaluation.Methods: A total of 241 patients with MM (146 males, 95 females; R-ISS stage I: 111 cases, stage II: 74 cases, stage III: 56 cases) and 50 healthy individuals were included in this study. Medical records were reviewed for staging. Interleukin-1 (IL-1), interleukin-2 receptor (IL-2R), interleukin-8 (IL-8), and tumor necrosis factor-alpha (TNF-α) were detected by chemiluminescence method, IL-38 was detected by enzyme-linked immunosorbent assay (ELISA). Immunoglobulins, free light chains (FLC) and β 2-microglobulin (β 2-MG) were detected by immune nephelometry, and multiple biochemical indicators were detected by automatic biochemical analyzers.Results: Compared with healthy control group, IL-1, IL-2R, IL-8, and TNF-α were elevated in all three stages of MM. In contrast, compared with normal control group, IL-38 was significantly decreased in patients with MM. When the cut-off value of IL-38 was 18.61 pg/mL, the diagnostic efficacy for MM had a sensitivity of 0.8176 and a specificity of 0.9000.Discussion: IL-38 exhibited decrease in MM patients (p< 0.0001). It also showed a gradual increase with disease improvement after effective treatment, IL-38 may be a potential biomarker for the diagnosis and prognostic assessment of MM.Keywords: interleukin 38, multiple myeloma, cytokine, blood disease, plasma cell disease